The Role of Personal Values in Forming the AI Ethics of Prospective Accountants - Latifah, Lyna; Setiyani, Rediana; Arief, Sandy; Susilowati, Nurdian (ETHICS IN PROGRESS, 2023)
This study aims to discuss how to form AI (Artificial Intelligence) ethical behavior with insight into the personal and organizational values of prospective accountants. This was a quantitative survey method. The sampling technique with a saturated sample was used as the research sample. Partial Least Square (PLS) analysis was conducted on 421 data points using WarpPLS software. The study results show that organizational and personal values significantly positively affect the intention of prospective accountant students to engage in AI ethics. Organizational values have a positive effect on the personal values of prospective accounting students. Intentions had a significant effect on AI ethics. Personal values did not play a role in mediating the impact of organizational values on intentions toward AI ethics. Intention succeeds in mediating the influence of personal values on the intention to engage in AI ethics among prospective accountant students. The findings referred to are very applicable to be implemented in different cultural settings due to the personal and organizational values tend to be implemented in general situation and condition. The findings provide universal outlook that values within organizations have an essential role in enhancing future accountants to be ethical in respect to AI.